(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper aims at exploring the school choice patterns in the chosenschool in detail. It does not draw generalizations of any kinds and usesqualitative research methodology of research although some quantitative data isalso collected to assist data analysis. The researcher’s findings suggest thatparents are primarily considering academic factors while making the school choice.School choice is primarily a family process with parents consulting theirchildren while making the final decision. The findings also suggest that on anaverage parents are choosing from amongst two to three schools while takingtheir decision and teachers are cited as the most useful sources of informationby parents while the local newspapers which are the preferred tools ofmarketing for the school management are least favored.